STUDI SISTEM USAHATANI PADI BERBASIS AGRIBISNIS DI KABUPATEN SERANG (KECAMATAN PONTANG, KASEMEN DAN TIRTAYASA) - Suhendar, Dusep; Utama, Putra; Uzliawati, Lia (Lampung University)
This research intends to detemine paddy farming in Serang District, including the application of insus type D, production per season, and the effect of such tehcnological application to the production and income of paddy farming. The study employs survey method while the research sites are purposevely selected, i.e.Pontang, Kasemen, and Tirtayasa subdistricts. The study interveiwed 30 farmers who were selected using stratified random sampling, i.e: board and regular member of farmers group. The study suggests that production of paddy farming has improved by 94% after using insus type D technology. Average production of irrigated paddy farming is 61,2 quintal per hectare of GKP which is only 68% of the intended production target, i.e. 90 quintal per hectare per season. Break Even Point is reaced at Rp. 2.468.449, or production of 2.194 kg, or at farm size of 0,36 ha, with ratio of revenue to cost or R/C at 1,74. In conclusion, the tehcnology is proved to be profitable for farmers.